Islamic Economic Perspectives on Sustainable Production and Environmental Stewardship - Hartanto, Selamet; Amir Sup, Devid Frastiawan (Journal of Economicate Studies, 2021)
This article examines the interconnection between production and environmental sustainability through the lens of Islamic economics. It explores how core Islamic principles such as khilāfah (stewardship), mīzān (balance), maṣlaḥah (public interest), and ʿadl (justice) provide an ethical foundation for sustainable economic behavior. Using a qualitative approach rooted in document analysis, the study synthesizes classical Islamic teachings with contemporary environmental policy and sustainability science. The findings highlight the potential for operationalizing Islamic ethics through green sukuk, environmental waqf, and Shariah-based policy reforms. Unlike secular models that rely on external enforcement, Islamic ethics embed ecological care within spiritual obligations. The study offers a normative and practical framework that redefines production as a trust-oriented and ecologically responsible process. It contributes both theoretically and practically to developing faith-based models of sustainability, urging policymakers and institutions to integrate Islamic values into environmental governance and production systems.